Image guided radiation therapy boost in combination with high-dose-rate intracavitary brachytherapy for the treatment of cervical cancer - Wang, Xianliang; Li, Jie; Wang, Pei; Yuan, Ke; Yin, Gang; Wan, Bin (Journal of Contemporary Brachytherapy, 2016)
Purpose : The purpose of this study was to demonstrate the dosimetric and clinical feasibility of image guided radiation therapy (IGRT) combined with high-dose-rate (HDR) intracavitary brachytherapy (ICBT) to improve dose distribution in cervical cancer treatment. Material and methods: For 42 cervical cancer patients, magnetic resonance imaging (MRI) scans were acquired after completion of whole pelvic irradiation 45-46 Gy and 5 fractions of B + I (ICBT + IGRT) treatment were subsequently received. The high risk clinical target volume (HRCTV), intermediate risk clinical target volume (IRCTV), bladder, rectum, and sigmoid were contoured on the computed tomography (CT) scans. The total planning aim doses for HRCTV was D 90% > 85 Gy, whilst constraints for rectum and sigmoid were D 2cc < 75 Gy and D 2cc < 90 Gy for bladder in terms of an equivalent dose in 2 Gy (EQD2) for external beam radiotherapy (EBRT) and brachytherapy boost. The IGRT plan was optimized on top of the ICBT dose distribution. A dosimetric comparison was made between B + I and optimized ICBT (O-ICBT) only. Results: The mean D 90% of HRCTV was comparable for B + I and O-ICBT (p = 0.82). For B + I plan, HRCTV D100%, IRCTV D 100% , and IRCTV D 90% were significantly increased by a mean of 10.52 Gy, 5.61 Gy, and 2.70 Gy, respectively (p < 0.01). The D 2cc for bladder, rectum, and sigmoid were lower by a mean of 21.36, 6.78, and 10.65 Gy, respectively (p < 0.01). The mean rectum V60 Gy value over 42 patients was almost the same for both techniques but for bladder and sigmoid B + I had higher V60 Gy mean values as compared with the O-ICBT. Conclusions : B + I can improve dose distribution in cervical cancer treatment; it could be useful for tumors extended beyond the reach of intracavitary/interstitial brachytherapy (IC/ISBT) or for centers that are inexperienced or ill-equipped with IC/ISBT techniques. Additional confirmatory prospective studies with larger numbers of patients and longer follow-up are required to validate the durability.